Breaking and dissipation of ocean surface waves - Babanin, Alexander V., 1960- (Cambridge : Cambridge University Press, 2011)
Wave breaking represents one of the most interesting and challenging problems for fluid mechanics and physical oceanography. Over the last 15 years our understanding has undergone a dramatic leap forward, and wave breaking has emerged as a process whose physics is clarified and quantified. Ocean wave breaking plays the primary role in the air-sea exchange of momentum, mass and heat, and it is of significant importance for ocean remote sensing, coastal and ocean engineering, navigation and other practical applications. This book outlines the state of the art in our understanding of wave breaking and presents the main outstanding problems. It is a valuable resource for anyone interested in this topic: researchers, modellers, forecasters, engineers and graduate students in physical oceanography, meteorology and ocean engineering.
Title from publisher's bibliographic system (viewed on 24 Feb 2016).
Keywords: Ocean waves -- Measurement; Ocean waves -- Simulation methods